Unraveling the anoikis-cancer nexus: a bibliometric analysis of research trends and mechanisms - Junjie Jiang; Wei Peng; Nianzhe Sun; Deze Zhao; Weifang Cui; Yuwei Lai; Chunfang Zhang; Chaojun Duan; Wei Zeng (Future Science OA)
Background Cancer, influenced by genetics and the environment, involves anoikis, a cell death mechanism upon extracellular matrix detachment crucial for metastasis. Understanding this relationship is key for therapy. We analyze cancer and anoikis trends using bibliometrics.Methods A search was conducted from Web of Science Core, PubMed, Scopus and non-English databases such as the CNKI (inception- 21 December 2024). Data analysis employed Microsoft Excel, VOSviewer, CiteSpace, R software, and the online platform (https://bibliometric.com/).Results 2510 publications were retrieved, with a significant increase in the last decade. China led, the University of Texas system was productive, and the Oncogene Journal was popular. Breast, and colorectal cancers were frequently studied. Among them, representative tumor-related mechanisms were identified, commonalities such as (EMT, ECM, autophagy) and respective specific mechanisms were summarized.Conclusion This bibliometric analysis highlights rapid advances in anoikis research in cancer, emphasizing EMT and FAK pathways’ translational potential, guiding targeted therapies, and improving cancer treatment outcomes.